A cross-sectional survey examining motivation and beliefs to participating in a web-based prospective cohort study on nutrition and health among individuals with a low socioeconomic status - Mélina Côté; Stéphanie Harrison; Annie Lapointe; Catherine Laramée; Sophie Desroches; Simone Lemieux; Benoît Lamarche; Ariane Bélanger-Gravel (BMC, 2020)
Abstract Background Prospective cohort studies may support public health efforts in reducing health inequalities. However, individuals with a low socioeconomic status (SES) are generally underrepresented in health research. This study aimed to examine the intention and determinants of intention of individuals with a low SES towards participation in a Web-based prospective project on nutrition and health (NutriQuébec) in order to develop recruitment and retention strategies. Methods A cross-sectional survey based on the Theory of planned behaviour was conducted in the Province of Québec, Canada. Low SES individuals (high school or less and annual household income < $55,000 CAN) were recruited through a Web panel of a polling firm to assess intention, attitude, subjective norm and perceived behavioural control (PBC) towards participation in the NutriQuébec project. Linear regression and logistic regression analyses were conducted. Results Mean age of respondents (184 women, 141 men) was 57.6 y (SD = 13.6). Attitude (ß = 0.54, 95%CI: 0.41-0.68) and PBC (ß = 0.50, 95%CI: 0.37-0.63) were significantly associated with intention. Participants who agreed that participating in the study would contribute to an improvement in 1) collective health (odds ratio [OR] = 2.15, 95%CI: 1.27-3.64) and in 2) one's lifestyle habits (OR = 1.70, 95%CI: 1.04-2.78) were more likely to express positive intention compared to participants who did not agree with these statements. Participants who agreed to participate in the study even 1) in the absence of a financial incentive (OR = 1.43, 95%CI: 1.04-1.99) and even 2) if the completion of questionnaires took up to two hours (OR = 1.78, 95%CI: 1.27-2.48) were also more likely to express high intention. Receiving a personalized brief health assessment (OR = 1.61, 95%CI: 1.13-2.30) and the use of simple questions in the questionnaires (OR = 1.54, 95%CI: 1.05-2.25) were facilitating factors associated with high intention. Participants believing that participation would be too time-consuming were less likely to have positive intention (OR = 0.57, 95%CI: 0.43-0.75). Conclusions The development of a positive attitude and a high PBC towards participation in the NutriQuébec project will be necessary to obtain representative data of low SES adults.